(untitled) (Sustainable Development Insights, 2026)
This study aims to map the intellectual structure, thematic evolution, and emerging research directions in sustainable logistics through a bibliometric analysis of green practices, key challenges, and innovation trends. Data were collected from the Scopus database and analyzed using VOSviewer and Bibliometrix to examine keyword co-occurrence, thematic clusters, and temporal developments. The findings reveal that sustainable development, sustainability, and logistics constitute the central foundation of the field, with strong emphasis on green supply chain management and environmental impact mitigation. Early research predominantly focused on emission control and environmental measurement, while recent studies show a shift toward innovation-driven approaches, including digital technologies, circular practices, and data-based decision-making. Despite this progression, emerging themes such as machine learning and information management remain less integrated into the core discourse. This study contributes by providing a comprehensive and structured understanding of sustainable logistics research, highlighting the interconnected roles of green practices, operational challenges, and innovation. The results offer insights for academics and practitioners in identifying future research opportunities and developing more integrated and forward-looking sustainable logistics strategies.